Independensi dan Akuntabilitas Mahkamah Konstitusi dalam Sistem Ketatanegaraan di Indonesia - Farah Syah Rezah; Andi Tenri Sapada (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze the independence and accountability of the Constitutional Court in the constitutional system in Indonesia. This study uses a normative juridical method with a statute approach. The collection of primary, secondary, and tertiary legal materials is carried out using literature study techniques. The collected legal material is analyzed using qualitative data analysis methods to describe the problem and answer study purposes. The results show that the Constitutional Court acts as the interpreter and guardian of the constitution. In addition, the Constitutional Court also acts as a guardian of human rights, citizens’ constitutional rights, and democracy. Furthermore, independence and accountability in a judicial process are like two sides of a coin. These cannot be separated because the two principles complement each other. Although the Constitutional Court has implemented duties and functions based on the principle of accountability. However, the independence of the Constitutional Court as the executor of Judicial Power has finally been lost. The Constitutional Court is now a judicial institution whose position is limited to sub-ordination from the other spheres of State Power which proposes Judges to fill in the Constitutional Court. Therefore, it is recommended that Constitutional Judges maintain their independence even though their positions result from proposals by other spheres of State Power. It is also recommended that the President and the House of Representatives uphold the mechanism of checks and balances between spheres of state power based on democratic principles. In this case, to realize the ideals of a law-based and democratic-based state for the sake of a more recognized national and state life.